Economic and financial aspects of social security : an international survey - Richardson, J. Henry (London : George Allen & Unwin Ltd., 1960)
In this book, the author's survey is timely in directing attention to those basic principles and methods which are essential for sound progress. Specially valuable is the chapter which considers what proportion of the national income can be afforded for social security, and also that on the alternatives of financing by accumulating large funds or by 'pay-as-you-go' methods. He further emphasizes the flexibility of private occupational schemes and insurance to supplement basic State provision. Particularly, attention is directed to age and retirement; and discusses remedies for poverty arising from sickness and large families with low incomes.
Includes index.
Includes bibliographical references: p. 247-254.
ne 15/05/2018
Loans
Keywords: Social Security